Total Cholesterol and the Risk of Parkinson's Disease: A Review for Some New Findings - Gang Hu (Parkinson's Disease)
The studies on the association between serum cholesterol level and the risks of neurodegenerative diseases risk are debated. Some prospective studies have found that high serum cholesterol may increase the risks of dementia/Alzheimer's disease and ischemic stroke. However, other studies have found no association or a decreased risk of hemorrhagic stroke with increasing levels of serum total cholesterol. Little is known about the association between serum total cholesterol or a history of hypercholesterolemia and Parkinson's disease (PD) risk. Only a few case-control studies and four prospective epidemiological studies have examined this association, but the results are inconsistent. An inverse association between serum total cholesterol and the risk of PD has been found in one prospective study; however, no significant association is reported in the case-control studies and other two prospective studies. Recently, one large prospective study from Finland suggests that high total cholesterol at baseline is associated with an increased risk of PD. Further studies, especially large clinical trials, are needed.